Varying roles of glucoregulatory function measures in postprandial cognition following milk consumption. - Anderson, Jason R.; Maki, Kevin C.; Palacios, Orsolya M.; Edirisinghe, Indika; Burton-Freeman, Britt; Spitznagel, Mary Beth (European Journal of Nutrition, 2021)
Purpose: Past work suggests milk consumption may facilitate cognition in children and college students with higher fasting glucose compared to other beverages (e.g., fruit juice). However, no studies have evaluated this phenomenon in adults, or considered other measures of glucoregulatory function. This open-label study assessed the role of glucoregulatory function in postprandial cognition after milk intake in adults. We hypothesized participants with lower fasting or post-consumption plasma glucose following a glucose excursion challenge (glucose response) would demonstrate better cognition following beverages of higher (juice) versus lower (milk) or no (water) glycemic content. Methods: Forty-four nondiabetic, overnight-fasted adults attended three laboratory visits, ingesting 237 mL of 2% fat milk, apple juice, or water at each visit in a randomized, counterbalanced, crossover design. Participants completed cognitive testing (CNS Vital Signs) at baseline and 30, 90, and 150 min post-ingestion; primary outcomes were CNS Vital Signs composite scores. Fasting and post-consumption plasma glucose levels were assessed, with glucose response indexed as the change in plasma glucose from baseline to 30 min after juice (ΔGlucose). Results: Mixed modeling revealed participants with higher fasting glucose demonstrated better complex attention after water versus juice at 30 min, but better performance after juice versus water at 150 min (p = 0.02). Participants with a larger ΔGlucose demonstrated better processing speed (p = 0.01) 30 min after milk versus water; this effect also reversed at 150 min. Conclusion: Different methods of measuring glucoregulatory function reveal its differing roles in postprandial cognition. Time since ingestion may also determine which beverages best optimize cognition.